THE LEXICAL UNIT “HOSPITALITY” IN ENGLISH LINGUOCULTURE - Saxibova Dilrabo Ergashevna (International Journal of Literature and Language Studies, 2026)
In recent years, the concept of linguoculture has been widely used in the modern world. This article provides a comprehensive analysis of the linguocultural aspects of the lexical unit “hospitality,” which occupies an important place in English linguoculture. Particular attention is paid to its semantic features as the main focus of the study. The research examines how the concept of hospitality is reflected in the national values, traditions, customs, and communicative behavior of English-speaking people. In addition, the lexical meanings of this unit are explored in detail. The findings demonstrate that the concept of “hospitality” should not be viewed solely as the act of welcoming guests. Rather, it represents an important cultural value associated with respect, politeness, tolerance, sincerity, and the strengthening of social relationships. Furthermore, the article highlights both the common and distinctive features of hospitality in English and Uzbek linguocultures through a comparative perspective, emphasizing its role in intercultural communication.